COVID-19: public health management of the first two confirmed cases identified in the UK. (2020) - Holden, B.; Quinney, A.; Padfield, S.; Morton, W.; Coles, S.; Manley, P.; Wensley, A.; Hutchinson, C.; Lillie, P. J.; Duncan, C. J. A.; Schmid, M. L.; Li, A.; et al.
Abstract: We report key learning from the public health management of the first two confirmed cases of COVID-19 identified in the UK. The first case imported, and the second associated with probable person-to-person transmission within the UK. Contact tracing was complex and fast-moving. Potential exposures for both cases were reviewed, and 52 contacts were identified. No further confirmed COVID-19 cases have been linked epidemiologically to these two cases. As steps are made to enhance contact tracing across the UK, the lessons learned from earlier contact tracing during the country's containment phase are particularly important and timely.